Exploring the Shift Toward Sustainable Finance and Financial Reporting: An Extensive Analysis of Emerging Trends, Research Patterns, and Implications for Global Sustainability - Sari Mujiani (Westscience Press, 2023)
This study presents a comprehensive analysis of the shift toward sustainable finance and financial reporting, examining emerging trends, research patterns, and their implications for global sustainability. The research employs bibliometric analysis to explore the scholarly landscape, identify key areas of focus, and understand the interconnections within the field. The study analyzes publication output over time, identifies influential journals, authors, and institutions, and investigates citation networks. Through content analysis, it identifies emerging research themes and topics within sustainable finance and financial reporting. Additionally, the study explores the implications of sustainable finance and financial reporting for promoting global sustainability and sustainable development. The findings highlight a steady growth in research publications in the field, reflecting the increasing interest in sustainable finance and financial reporting. Key journals, authors, and institutions contributing to the field are identified, indicating the thought leadership and expertise in sustainable finance and financial reporting. Highly cited articles and influential authors shape the discourse and provide valuable references for further research.